Effects of N-Acetylcysteine Supplementation on Semen Analysis, Hormonal Profile and Spontaneous Pregnancy Rate in Idiopathic Infertile Men: Before and After Clinical Trial - Benjamongkolchai, Kirana; Phaliwong, Paweena; Kim, Jenny; Prasongvej , Pichita; Smanchat , Buppa; Prommas, Sinart; Bhamarapravatana , Kornkarn; Suwannarurk , Komsun (Siriraj Medical Journal, 2024)
Objective: To compare sperm quality and quantity, hormonal profiles and spontaneous pregnancy rates before and after administering a 3 months course of N-Acetylcysteine (NAC) Material and Methods: This prospective clinical trial was conducted at the Infertility Unit of the Obstetrics and Gynecology Department at Bhumibol Adulyadej Hospital, Thailand. The study period was from June 1, 2023 to September 30, 2023. Subjects were idiopathic infertile males aged between 20 and 50 years old. All subjects received 600 mg of NAC orally per day. Semen analysis (SA) and male hormonal profiles (MHP; testosterone, LH, FSH and prolactin) were performed before and three months after NAC administration. Demographic, clinical characters and laboratory change were recorded. Results: The 92 participants were recruited. The mean age of couples was 34.5 years old. The average duration of infertility was 3.6 years. Increase of semen volume (2.1 vs 2.4 ml, p < 0.001), semen concentration (30.5 vs 43.1 x 106/mL, p < 0.001), total motility (59.57 vs 72.38 %, p < 0.001), progressive motility (59 vs 69.8 %, p < 0.001), normozoospermia (60 vs 83 %, p < 0.001), testosterone (452.8 vs 479.0 ng/dL, p = 0.038), LH (4.6 vs 5.3 mIU/mL, p = 0.004) and FSH (4.4 vs 4.6 mIU/mL, p = 0.009) were observed after three months of NAC administration. No changes in sperm morphology and prolactin level. One-third (27/92) of each participant’s spouse conceived spontaneously. Conclusion: NAC potentially enhances male hormonal profiles, sperm quality and quantity with an impressive spontaneous pregnancy rate.